Naked eye instant reversible sensing of Cu2+ and its in situ imaging in live brine shrimp Artemia1. Issue 16 (21st August 2015) - Nair, Ratish R.; Raju, M.; Patel, Neha P.; Raval, Ishan H.; Suresh, E.; Haldar, Soumya; Chatterjee, Pabitra B.
<x xml:space="preserve">Abstract</x> A Cu2+-specific reversible chemosensor capable of showing a naked eye detectable instant change in colour in the presence of as low as 30 ppb of Cu2+ was designed. Utilizing brine shrimp Artemia, the LOD could be improved further to 10 ppb through bio-accumulation of Cu2+.